An Exceptional Case of Full-thickness Macular Hole Closure in a Patient with Behçet Disease. (February 2014) - Uçar, Didar; Atalay, Eray; Özyazgan, Yilmaz; Özkök, Ahmet; Yıldırım, Yeliz
Abstract Purpose: To present a case of a full-thickness macular hole closure in a patient with Behcet uveitis Design: A 23-year-old-male patient with Behcet Disease had clinically inactive uveitis with topical steroids, oral azathiopurine and cyclosporine until he developed a retinal infiltrate in the left eye which evolved into a full-thickness macular hole during the follow-up. Methods: Strict control of inflammation and subsequent vitrectomy was planned. Meanwhile another attack of panuveitis developed in the left eye and subcutaneous Interferon alfa-2b interferon treatment was initiated. Results: After 2 months, the patient was clinically inactive with complete closure of the macular hole. Conclusions: Strict control of inflammation may result in closure of the macular hole and avoid the need for vitrectomy.